Pengaruh Kompetensi Pedagogik dan Profesional Guru Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Faraid Kelas IX MTs. Tarbiyatut Tholabah Lamongan - Imam Azhar (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
This article aims to analyze the influence of pedagogical and professional competence of teachers on student learning outcomes in the subjects of the chapter sections of the IX class MTs heirs. Tarbiyatut Tholabah kranji is going to flee Lamongan in the academic year 2017/2018. The type of research is quantitative correlational research. According to Fox in Azhar's book, correlational research is research that is designed to determine the degree of relationship of different variables in one population. The description in this study is about the effect of teacher's pedagogic and professional competence on student learning outcomes in IX grade MTs. Tarbiyatut tholabah. Based on the research activities, it was found that the effect of pedagogical competence on student learning outcomes was 42.7%. While the rest is 57.3%. The percentage effect of learning interest on student learning outcomes is 32.2%. While the remaining 67.8%.